Time Interval From Early-Term Antenatal Corticosteroids Administration to Delivery and the Impact on Neonatal Outcomes - Li, Jing; Zhang, Jing; Hao, Qingfei; Du, Yanna; Lu, Jie; Chen, Haoming; Cheng, Xiuyong (Frontiers in Pediatrics, 2022)
Objectives To determine the association between the time interval from antenatal corticosteroids administration to delivery and neonatal complications in diabetic mothers undergoing early term (37+0 to 38+6 weeks) scheduled cesarean section (ETSCS). Study Design A retrospective cohort study of women with any form of diabetes in pregnancy undergoing ETSCS was included. Cases were stratified into the following groups based on the time interval from the first dose of corticosteroids administration to delivery: <2, 2–7, and >7 days. Women undergoing ETSCS, who did not receive corticosteroids were included as controls. We assessed the association between the time interval and neonatal outcomes in a multivariate regression model that controlled for potential confounders. Primary outcomes were the incidence of respiratory distress syndrome (RDS)/transient tachypnea of the newborn (TTN) and neonatal hypoglycemia. Results The study cohort comprised 1,165 neonates. Of those, 159 (13.6%) were delivered within 2 days of maternal corticosteroids administration, 131 (11.2%) were delivered within 2–7 days after maternal corticosteroids administration, and 137 (11.8%) delivered more than 7 days after maternal corticosteroids administration. The remaining 738 (63.3%) were not exposed to corticosteroids. Multivariate analysis demonstrated that delivery within any time of antenatal corticosteroids administration was not associated with decreased risks of RDS/TTN. The risk of neonatal hypoglycemia was highest in the delivery of <2 days group (adjusted odds ratio [aOR]: 2.684, 95% confidence interval [CI]: 1.647–4.374 for control group; aOR: 2.827, 95% CI: 1.250–6.392 for delivery 2–7 days group; aOR:2.975, 95% CI: 1.265–6.996 for delivery >7 days group). Conclusions Corticosteroids treatment for diabetic mothers undergoing ETSCS was not associated with beneficial neonatal respiratory outcomes. In addition, delivery, <2 days after antenatal corticosteroids administration was associated with an increased risk of neonatal hypoglycemia.